Skin scarring: Latest update on objective assessment and optimal management - Basson, Rubinder; Bayat, Ardeshir (Frontiers in Medicine, 2022)
Although skin scarring is considered by some to be a minor, unavoidable consequence in response to skin injury, for many patients, cosmetically unsightly scars may cause uncomfortable symptoms and loss of function plus significant psycho-social distress. Despite their high prevalence and commonality, defining skin scars and their optimal management has proven problematic. Therefore, a literature search to assess the current evidence-base for scarring treatment options was conducted, and only those deemed Levels of Evidence 1 or 2 were included. Understanding the spectrum of skin scarring in the first instance is imperative, and is mainly comprised of four distinct endotypes; Stretched (flat), Contracted, Atrophic, and Raised for which the acronym S.C.A.R. may be used. Traditionally, scar assessment and response to therapy has employed the use of subjective scar scales, although these are now being superseded by non-invasive, objective and quantitative measurement devices. Treatment options will vary depending on the specific scar endotype, but fall under one of 3 main categories: (1) Leave alone, (2) Non-invasive, (3) Invasive management. Non-invasive (mostly topical) management of skin scarring remains the most accessible, as many formulations are over-the-counter, and include silicone-based, onion extract-based, and green tea-based, however out of the 52 studies identified, only 28 had statistically significant positive outcomes. Invasive treatment options includes intralesional injections with steroids, 5-FU, PDT, and laser with surgical scar excision as a last resort especially in keloid scar management unless combined with an appropriate adjuvant therapy. In summary, scar management is a rapidly changing field with an unmet need to date for a structured and validated approach.